PENGARUH HARGA, LOKASI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN CV. ZAFIRA TEKNIK PEKANBARU - Ansori, Putra Budi (Eko dan Bisnis: Riau Economic and Business Review, 2020)
This research was conducted in the research conducted at CV.Zafira Teknik Pekanbaru, SM.Amin, Pekanbaru City in 2019. This study was to determine the effect of price, location and product quality on consumer purchasing decisions CV. Zafira Teknik Pekanbaru. The population in this study are consumers who buy doors and repair doors at CV. Zafira Teknik Pekanbaru 2018 is 1,188 people. With a sample of 92 people with a sampling method based on purposive sampling. From the analysis of multiple linear regression equation was formulated:  Y= 2,620 + 0,371X1+ 0,143X2 + 0,336X3.  The results of the t test (partial test) obtained the value of t arithmetic for Price/ X1 (5,077) and product quality/ X3 (3,208) greater than t table of 1,98729, then it has a significant effect on consumer purchasing decisions CV. Zafira Teknik Pekanbaru. Whereas the Location /X2 variable does not significantly influence the consumer purchasing decision variable CV. Zafira Teknik Pekanbaru, this is because the value of t_count (1.340) <t_tabel (1.98729) . F Test Results (joint test), it is concluded that  F count  is 28.304> F table 2.71 so that simultaneously   the variables of Price, location, and product quality on consumer purchasing decisions CV. Zafira Teknik Pekanbaru. . There are contribution the influence of variables of Price, location, and product quality on consumer purchasing decisions CV. Zafira Teknik Pekanbaru of Obtained value of Adjusted R Square equal to 0,471 or 47,1% and 52,9 % influenced by the other factors that are not pursuing in this research. So this research to strengthen previous studies